The student’s perception on effectiveness of internship program in Universiti Teknologi Mara Cawangan Melaka Kampus Bandaraya Melaka / Flora Lenjai Noel - Noel, Flora Lenjai (Faculty of Business and Management, 2018)
This research explores the student’s perceptions on the effectiveness of internship program in Universiti Teknologi MARA Cawangan Melaka Kampus Bandaraya Melaka. The survey was conducted to determine the significance and influence of underpinnings of the relationship between pre-placement activities, assistance provided by staff internship unit and the support provided by Host Company towards the effectiveness of internship program in Universiti Teknologi MARA Cawangan Melaka Kampus Bandaraya Melaka. A total of 186 usable questionnaires were distributed and 136 were obtained.